1996
DOI: 10.1079/bjn19960078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding and short-term fasting on water and electrolyte turnover in female mink (Mustela vison)

Abstract: Daily (24 h) rates of water and electrolyte turnover were measured in a conventional balance study in ten adult female pastel mink (Mustela &on) given free access to a standard mink feed for a l-week conditioning period, followed by a 4 d experimental period and a 2 d fasting period. Drinking water was available throughout. In addition, the completeness of urine collection and the fraction of urine collected with the faeces were determined using a new experimental technique based on 24 h recoveries of specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Although urine volume decreased significantly after food was withheld from the cats, the recoveries of 14 C-inulin were not significantly different from 100 during the 2-day feed restriction period. In a similar study with mink housed in standard wire floor metabolism cages, WAMBERG et al (1996b) found recoveries of 3 H-p-aminohippuric acid and 14 Cinulin in the urine of mink in the fed state of 71 and 68%, respectively. These authors found a total recovery (urinary plus fecal water) for each radioactively labelled compound of 77%.…”
Section: Study 1: Accuracy Of Urine Collection In Adult Catsmentioning
confidence: 85%
See 2 more Smart Citations
“…Although urine volume decreased significantly after food was withheld from the cats, the recoveries of 14 C-inulin were not significantly different from 100 during the 2-day feed restriction period. In a similar study with mink housed in standard wire floor metabolism cages, WAMBERG et al (1996b) found recoveries of 3 H-p-aminohippuric acid and 14 Cinulin in the urine of mink in the fed state of 71 and 68%, respectively. These authors found a total recovery (urinary plus fecal water) for each radioactively labelled compound of 77%.…”
Section: Study 1: Accuracy Of Urine Collection In Adult Catsmentioning
confidence: 85%
“…The scintillation fluid consisted of 67 parts toluene and 33 parts triton X-100 containing 0.4% 2,5-diphenyloxazole (PPO). Fecal water was obtained by centrifugation (3100 g, 15 min, 5°C) and 0.5-ml samples were decolourized with hydrogen peroxide according to the procedure described by WAMBERG et al (1996b). All samples were measured in duplicate and corrections were made for sample quenching and dry matter content.…”
Section: Radioisotopes and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…U.K. Home Office guidelines state that a licence is not required for food deprivation under 24 h, for animals weighing 100 g or more (female mink weigh about 800 g). Laboratory studies also show that (1) mink fasted for 2 days retain full control of renal water and electrolyte metabolism (Wamberg et al 1996), (2) 24-h fasting does not cause stomach ulceration (Harri et al 1995), and (3) weekly 24-h fasts are normal practice on some U.K. fur farms (Mason 1993). However, there is little doubt that using food as a resource in this way made the animals hungry, and 'starve days' have recently been proscribed on farms.…”
Section: Ethical Notementioning
confidence: 99%
“…Recording of drinking water intake and quantitative collection of feed residues and excreta took place once daily between 8.30 and 12.00 a.m., and the pooled amount collected from each period was stored at -18°C until analysis. The collection procedures have been described in detail by Wamberg et al (1996). Each balance period included a 22-h respiration experiment by means of indirect calorimetry in an open-air circulation system.…”
Section: Balance and Respiration Experimentsmentioning
confidence: 99%